2015
DOI: 10.1002/hec.3147
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns among Entrants and Incumbents in the Home Health Market after the Prospective Payment System was Implemented

Abstract: Home health care expenditures were the fastest growing part of Medicare from 2001-2009, despite the implementation of prospective payment. Prior research has shown that home health agencies adopted two specific strategies to take advantage of Medicare policies: provide at least 10 therapy visits to get an enormous marginal payment and recertify patients for additional episodes. We study whether there is heterogeneity in the adoption of those strategic behaviors between home health agency entrants and incumbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…3 This was a key factor leading to high, unwarranted regional variation in SNF and HHA spending. 4,5 Because the new SNF and HHA payment models base payments on patient characteristics rather than the delivery of therapy, the net outcome is that SNFs and HHAs that care for patients with more severe illness or clinical problems will receive more dollars and those that care for patients in better health who can tolerate high levels of therapy will receive fewer dollars.…”
Section: Reforming Postacute Care Paymentsmentioning
confidence: 99%
“…3 This was a key factor leading to high, unwarranted regional variation in SNF and HHA spending. 4,5 Because the new SNF and HHA payment models base payments on patient characteristics rather than the delivery of therapy, the net outcome is that SNFs and HHAs that care for patients with more severe illness or clinical problems will receive more dollars and those that care for patients in better health who can tolerate high levels of therapy will receive fewer dollars.…”
Section: Reforming Postacute Care Paymentsmentioning
confidence: 99%
“…9 The intuition is that, with imperfect quality information, providers may compete on dimensions that boost revenue but hurt the quality of care. 10 The 2000 Medicare Prospective Payment System on home health care substantially increased the payment margin and attracted new entries in the industry (Kim & Norton, 2015).…”
Section: The Overall Impact Of the Hhc On Qualitymentioning
confidence: 99%
“…Home health care covers a wide range of post‐acute care, such as skilled nursing care, physical therapy, home health aide, and medical social work services. It is delivered in patients' homes and is considered a close substitute and efficient alternative to post‐acute care provided in hospitals and skilled nursing facilities (Kim & Norton, ). We focus on the home health care industry to study the interactive effect of CON and information disclosure for the following two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…As a possible explanation, they argue that there is less information asymmetry between supplier and user in home care services, in comparison to physician services-thus hampering providers to stimulate demand at will. Kim and Norton [39] concluded that new entrants, for-profit as well as nonprofit entrants, were more responsive to upward financial incentives, leading to more visits per episode and more recertified care episodes. Furthermore, for-profit entrants affected the behavior of incumbents one year after entrance, so that their entrance also had an indirect positive correlation with home care costs.…”
Section: Supply Factorsmentioning
confidence: 99%